2015
DOI: 10.1002/nbm.3261
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in chronic fatigue syndrome for severity‐dependent upregulation of prefrontal myelination that is independent of anxiety and depression

Abstract: White matter (WM) involvement in chronic fatigue syndrome (CFS) was assessed using voxel-based regressions of brain MRI against CFS severity scores and CFS duration in 25 subjects with CFS and 25 normal controls (NCs). As well as voxel-based morphometry, a novel voxel-based quantitative analysis of T1- and T2-weighted spin-echo (T1w and T2w) MRI signal level was performed. Severity scores included the Bell CFS disability scale and scores based on the 10 most common CFS symptoms. Hospital Anxiety and Depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 53 publications
8
80
0
Order By: Relevance
“…Although most VBM processing and analysis is automated in SPM, several methodological options remain for user specification,19 especially in analysis of longitudinal image data. Inconsistent VBM findings in CFS patients in previous studies6, 7, 12, 14 motivated us here to validate segmentation and optimize VBM methodology. The VBM atrophy simulation experiment demonstrated (1) that normalization to a study specific template performs better than direct normalization to the default template provided in SPM12; (2) when the sample size is small, a random effects one‐sample t‐test of longitudinal difference images, either by means of the Jacobian difference method or the direct difference between different time points, has higher sensitivity than a paired t‐test of images from two time points; (3) that creation of a single image representative of the two time points (within‐subject template) for the purpose of the shared final spatial normalization should involve similar normalizations of both raw images and the same processing steps.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although most VBM processing and analysis is automated in SPM, several methodological options remain for user specification,19 especially in analysis of longitudinal image data. Inconsistent VBM findings in CFS patients in previous studies6, 7, 12, 14 motivated us here to validate segmentation and optimize VBM methodology. The VBM atrophy simulation experiment demonstrated (1) that normalization to a study specific template performs better than direct normalization to the default template provided in SPM12; (2) when the sample size is small, a random effects one‐sample t‐test of longitudinal difference images, either by means of the Jacobian difference method or the direct difference between different time points, has higher sensitivity than a paired t‐test of images from two time points; (3) that creation of a single image representative of the two time points (within‐subject template) for the purpose of the shared final spatial normalization should involve similar normalizations of both raw images and the same processing steps.…”
Section: Discussionmentioning
confidence: 86%
“…CFS severity was measured by three scores: the Bell CFS disability score,15 a somatic symptom score (Somatic SS), and a neurological symptom score (Neuro SS) 14. The Somatic and Neuro SS were derived from self‐scores of the 10 most significant symptoms 16.…”
Section: Methodsmentioning
confidence: 99%
“…For example, system-dependent coupling of oscillations has fundamental importance to CNS function and may be strongly influenced by delays in conduction velocity and myelin plasticity. Changes to white matter have been reported in CFS (Puri et al, 2012), also associated with clinical measures (Barnden et al, 2011), and a severity-dependent increase in myelination has also been found (Barnden, Crouch, Kwiatek, Burnet, & Del Fante, 2015). Disruption to white matter could explain the relationship between abnormal eLORETA coherence patterns over largescale complex systems in CFS.…”
Section: Discussionmentioning
confidence: 94%
“…Compared to patients with depression, patients with ME and CFS have shown significantly lower scores on the SF-36, a different degree of disability and pattern of impairment [54]; different reporting of widespread body pain [55]; distinct brain physiology [56]; and differences in white matter volume [57]. These differences suggest that, although some patients also suffer from depression, as do some patients with other serious illnesses, ME and CFS are different from solely psychiatric illnesses such as major depressive disorder [58].…”
Section: Discussionmentioning
confidence: 99%